Decisão: perspectivas interdisciplinares - Carlos Henggeler Antunes (Documentos, 2007)
This book revisits the cycle of lectures on the subject of "Decision", organized by the III-UC, INESC Coimbra and FEUC, which took place in October and November 2005, with the participation of four internationally renowned scholars, Profs. Alexis Tsouki